Occupation Humaine De La Réserve De Faune Et De Flore Du Haut Bandama : Diagnostic Et Perspectives Pour Une Gestion Durable - Olivier, Dien Kouayé (European Scientific Journal, ESJ, 2018)
The Upper Bandama fauna and flora reserve, which is part of Côte d’Ivoire’s biodiversity conservation strategy, is threatened by the pressure of human activities. The purpose of this article is to make a socio-economic assessment of the exploitation of the natural resources of this protected area. Specifically, it is question of knowing the forms of activities which are developed there, the actors, the strategies of infiltration, and to determine the factors related to this occupation. Based on a data collection work that combines documentary research, semi-structured interviews and direct observation, artisanal gold mining, farming, poaching, fishing and collection of non-timber forest products have been identified as the major forms of degradation of this reserve. These activities involve different profiles of actors who have accessed the reserve under various conditions. They can be explained by the economic dynamism of the peripheral zone, the recomposition of this zone in the face of demographic pressure and land issues, the non-integration of the legal status of the reserve and the invisibility of the key actors. The study ends with perspectives for sustainable management of this reserve.